Bioflocculant production using palm oil mill and sago mill effluent as a fermentation feedstock: Characterization and mechanism of flocculation. (15th April 2020) - Hassimi, Abu Hasan; Ezril Hafiz, Razali; Muhamad, Mohd Hafizuddin; Sheikh Abdullah, Siti Rozaimah
Abstract: This study was conducted to examine the production of bioflocculants using agricultural wastewater as a fermentation feedstock under different temperatures and incubation times. The mechanism of flocculation was studied to gain a detailed understanding of the flocculation activity. The highest bioflocculant yield (2.03 g/L) at a temperature of 40 °C was produced in a palm oil mill effluent medium (BioF-POME). Bioflocculant produced from a fermented SME medium (BioF-SME) showed the highest activity. The flocculation tests for colour and turbidity removal from lake water indicated that BioF-SME and BioF-POME performed comparably to commercial alum. Analyses of the bioflocculants using liquid chromatography-mass spectrometry (LC-MS) found that the bioflocculants contained xylose and glucose. The mechanism study showed that flocculation occurred through charge neutralization and interparticle bridging between the bioflocculant polymer and the particles in the lake water. Thus, agricultural wastewater can be used as a fermentation feedstock for high-quality bioflocculants. Graphical abstract: Image 10995 Highlights: Agriculture wastewater as a bioflocculant fermentation media. Fermentation was investigated under different temperatures and incubation times. Performances of extracted bioflocculants were comparable to alum. Extracted bioflocculants contain xylose and glucose. Flocculation mechanism was through charge neutralization and interparticle bridging.